12y=-10x-60

Simple and best practice solution for 12y=-10x-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12y=-10x-60 equation:


Simplifying
12y = -10x + -60

Reorder the terms:
12y = -60 + -10x

Solving
12y = -60 + -10x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '12'.
y = -5 + -0.8333333333x

Simplifying
y = -5 + -0.8333333333x

See similar equations:

| -9x+l=-80 | | 2(3x-6)=6(x-6) | | 3x-8=2x-15 | | f(x)=(x+6)2+14 | | 5(x+23)= | | 62*26=x | | -.33(9x+18)= | | 6.3=-8+x | | 2x+5x-8=6 | | 5.7=-9+x | | 6x+5x-9=35 | | x^2+33x= | | x^2+33= | | 8d+9=4d+45 | | -5=x.4 | | x^2+24x= | | 4(x-9)=-21.6 | | 3/4(x+1)=20 | | 2(a+7)=29.4 | | -1.4=3c-8 | | -5.9+y=-4.7 | | xsquared+3x-9=0 | | 3y=6-9 | | (9x+8)(8x-9)= | | 6-n=-6-3n | | 3x+6-4x+12=12 | | 110=39.41+.25x | | 12=4x+5 | | (4x-3)(8x+6)= | | 5x+19=2x+1 | | 0.6-0.6(7-3)=1.5(2.8-1)-3 | | 5x+1+6=21 |

Equations solver categories